2021
DOI: 10.1016/j.cca.2021.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Covid-19 shutdown on glycemic testing and control

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused a halt to in-person ambulatory care. We evaluated how the reduction in access to care affected HbA1c testing and patient HbA1c levels. Methods HbA1c data from 11 institutions were extracted to compare testing volume and the percentage of abnormal results between a pre-pandemic period (January-June 2019, period 1) and a portion of the COVID-19 pandemic period (Jan-June 2020, period 2). HbA1c results great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…25 In the study by Sharma et al , the HbA1c request volumes from 11 institutions across the United States and Canada, decreased during March – May 2020 compared to 2019, and returned to baseline in June 2020. 21 Lum et al reviewed cancer cases from a large cancer registry in the United States. They compared the number of new cancer diagnoses made in 2020 to the case number in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…25 In the study by Sharma et al , the HbA1c request volumes from 11 institutions across the United States and Canada, decreased during March – May 2020 compared to 2019, and returned to baseline in June 2020. 21 Lum et al reviewed cancer cases from a large cancer registry in the United States. They compared the number of new cancer diagnoses made in 2020 to the case number in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, one study of private claims data documented a higher rate of inpatient admissions for diabetes complications in the postpandemic period through 2021. 26 Several studies found lower rates of hemoglobin A1c tests, 27,28 lower adherence to asthma medications for Medicare patients, 29 and a higher rate of discontinuation of chronic medications for patients in Massachusetts during the pandemic, 30 so some health systems and populations may have experienced greater disruptions to chronic condition care than our population of high-risk VA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Varying studies have shown that during the early months of the pandemic, the number of HbA1c tests performed on outpatients decreased by up to 70% [ 5 , 20 , 21 ]. The number of HbA1c tests was observed to have declined sharply in April 2020 and gradually increased thereafter globally [ 21 ].…”
Section: Discussionmentioning
confidence: 99%